Володимир Сосюра як баладист: до проблеми традиції і новаторства - Вишняк, М.Я. (Культура народов Причерноморья, 2014)
У статті простежується, роль і місце жанру балади в повоєнній творчості В.М.Сосюри в
літературному контексті, ії різновиди та художньо-індивідуальна специфіка. В статье прослеживается развитие, роль и место жанра баллады в послевоенном
творчестве В. М. Сосюры в литературном контексте, ее разновидность и художественно-
индивидуальная специфика. The article is dedicated to creativity of Vladimir Sosyura, Ukrainian Iyric poet, whose work is
characterized by variety of genres. His particular attention is focused on the use of ballad genre, which he used
at the beginning of his career, as weel as at the moments of hardships during World War II. But the poet worked
particularly active in this genre during the postwar years. Using the ballad tradition of Ukrainian romantic poet
and Taras Shevcenko and his own experience, Sosyura was able to create his own works of this genre that
characterized by specific innovation both in form and in content. Their feature – a fusion of lyrical self-interest
with the public, the assertion of universal ideals for which he sacrifices himself. Sosyura’s ballads are varied in
meaningfulness. They can be divided into two main groups – the historical and heroic and social sound. Story
plot of these works are usually built on general public events in which the hero is in the moment of the greatest
emotional stress. Ballads of the first group created by the poet during the Civil World War II. Ballads of the
second group are traditional, folk songs symbols and elements of fiction are used there. They are more romantic.
These include ballads about the exploits of people in the days of sorrow and their heroic deeds in the days of
peace. The basis of the last ones is facts of life. Despite the tragedy of the represented, Sosyura’s ballads include
optimistic tone. They share life truthfulness, coupled with the emotional narrative.